Strategi Komunikasi Penyuluh Agama dalam Menangani Konflik Rumah Tangga di Kantor Urusan Agama Ambulu Jember - Ashar, Salsabiela Muadz (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Communication strategy is an efficient and effective guide and preparation necessary to convey the message and ensure that the recipient can understand it in order to achieve certain goals at KUA AmbuluJember carried out by religious counselors to help deal with home conflicts ladder. The research focus is divided into two: 1) What is the communication strategy used by religious counselors in handling domestic conflicts at KUA AmbuluJember? 2) What are the supporting and inhibiting factors for extension workers religion in handling domestic conflicts at KUA AmbuluJember?. This research aims to 1) Find out what communication strategies are used by KUA Ambulu religious counselors in handling domestic conflicts ladder. 2) To find out supporting factors and inhibiting factors for extension workers religion in handling domestic conflicts at KUA AmbuluJember. This research uses descriptive qualitative methods, where method This will make it easier for researchers to conduct research in the field. Data was collected by means of interviews, observation and documentation. The results of this research are the communication strategies used by Religious counselors in handling domestic conflicts at KUA Ambulu are with interpersonal communication strategies that refer to dyadic communication and small group communication using online delivery techniques persuasive and uses dialogue in communication.